EVALUATiON OF FUNCTiONAL CAPABiLiTiES iN PRACTiCALLY HEALTHY TEENAGERS LiViNG iN EASTERN SiBERiA - O. YU. Katulskaya (Acta Biomedica Scientifica, 2012)
The article presents the results of examination, of teenagers schoolchildren, of 14—16 years old. who live in a town of Eastern. Siberia (by the example of Sayansk). According to the findings, 75,3 % of the teenagers have enough, adaptive capabilities. Performed, test for the responsiveness of the cardiovascular system, showed, that physiological response to the physical activity was observed, in most of examined, teenagers. The vascular type of the self-regulation of circulation of the blood that can testify to the circulation economization, was found, to be in 14,2 % of the teenagers.